Blood glucose homeostasis, birth weight, and pancreas of rat pups during pregnancy the mother is intervened with food substitution beef bone marrow - Tangkas, I Made; Putri, Linda Ayu Rizka; Hasanah, Hasanah (Nutrición Clínica y Dietética Hospitalaria, 2025)
Background: The growth of the intrauterine pancreas in the fetus is very dependent on the mother’s nutritional intake during pregnancy. Previous research on animal models found that mother rats during pregnancy who were given low-protein feed gave birth to offspring with lower pancreatic weight compared to rat offspring given normal diet. This study aims to evaluate the potential of feed nutrients substituted for bovine bone marrow in increasing intrauterine pancreatic growth with biomarkers of glucose homeostasis, birth weight and pancreatic weight in rat offspring. Methods: This study employs an experimental study with in vivo design. During pregnancy, the Sprague Dawley rat animal model used in this study was intervened with Low Protein Feed (LPF), Normal Feed (NF) and Bovine Bone Marrow Substitution Feed (BBMSF). All formulated feeds are made isocaloric. Results: there was a significant difference (α <0.05) in the blood glucose of rat offspring from mothers who were intervened with LPF, NF and BBMSF at the age of 60 days. Rat pups whose mothers were intervened with LPF, NF, and BBMSF during pregnancy had significant differences in body weight (α<0.05). There was no significant difference (α > 0.05) in the weight of the pancreas of rat offspring from mothers who were intervened with LPF, NF and BBMSF at the ages of 30 and 60 days. Conclusion: Rat pups from mothers who were intervened during pregnancy with bovine bone marrow substitute feed had a better ability to maintain blood glucose homeostasis, had a higher average birth weight and pancreatic weight compared to rat pups from NF and LPF mothers.